A qualitative study on the attitudes of women politicians toward their roles in politics: a case of Northern Cyprus - Artaç, Niyper Hayal; Oğurlu, Ebru (Frontiers in Psychology, 2024)
Introduction Politics is a mechanism of cooperation for the common interest of society. In this mechanism, each individual is expected to participate equally in the leadership and decision-making mechanisms. Women's participation in politics is essential for the spread of good governance and democracy. Globally, political participation is disaggregated by gender, with men's participation greater than women's. A lower representation of women in politics is also observed in Northern Cyprus. The attitudes or views of society and politicians may determine the political participation of women in leadership positions. This study examines the obstacles and determining factors that make it difficult for women to reach leadership positions even though their political role is increasing. Methods Semi-structured interviews were conducted with 21 female participants for this research. Eleven of them are female ministers in parliament and represent the three main political parties in the country. The remaining 10 female participants are also members of the central executive body of the three parties and the National Assembly. Results and discussion Women politicians believe that problems related to gender equality in politics prevent women from entering active politics and rising to leadership positions. Although there was no gender discrimination in Northern Cyprus means that women have gained equal rights with men in many areas, it was concluded that the traditional political culture keeps women out of politics.